Effect of duration of IBH on cumulative number of positive serum IgE values. - Jasmin Birras (11707271); Samuel J. White (10512181); Sigridur Jonsdottir (1303788); Ella N. Novotny (11707274); Anja Ziegler (11707277); A. Douglas Wilson (11707280); Rebecka Frey (3362939); Sigurbjörg Torsteinsdottir (11707283); Marcos Alcocer (8212260); Eliane Marti (157764) (2021)
Icelandic horses living in Sweden grouped according to how long they had been affected with IBH (< 4 years, 4–7 years or >7 years). No significant differences between the groups in the Kruskal-Wallis Multiple-Comparison Z-Value test. Green triangles identify horses that were born in Sweden and grey triangles those that were born in Iceland and exported to Sweden.